Feminist Intersectionality Research in Communications: Origins, Contributions and Tensions - Byerly,Carolyn M. (2017)
The text considers some of the important work in intersectionality that has been done by critical feminist and postcolonial scholars in media and other communication fields since the 1990s, focusing particularly on the kinds of problems they have examined and their contributions to feminist theory building. The discussion also explores some of the challenges and tensions that accompany scholarship conducted from a standpoint of intersectionality.